Sirt5 affects the metabolic remodeling of eosinophils by negatively regulating the level of succinylation modification of Pkm2 in eosinophilic chronic rhinosinusitis - Shun‐Yu Wu; Bo‐Yu Cai; Zhi‐Wen Cao; Tian‐Yu Wang; Cai‐Quan Liang; En‐Hong Xu; Hu Peng; Jianchun‐Liao; Huan‐Hai Liu (World Journal of Otorhinolaryngology-Head and Neck Surgery)
Abstract Objectives This study aims to investigate the role of Sirt5 in regulating eosinophil maturation and activation, specifically focusing on primary eosinophils in mice at the genetic level. Additionally, the study aims to elucidate the underlying mechanism of Sirt5 in eosinophilic inflammation metabolism and identify potential drug targets for the treatment of chronic sinusitis. The findings of this study will provide new insights and a solid theoretical basis for the development of novel therapeutic strategies for eosinophilic chronic rhinosinusitis (eCRS). Methods Our study investigated the role of Sirt5 gene expression in both non‐eCRS and eCRS. We examined the correlation between Sirt5 gene expression and disease severity as well as eosinophil infiltration. Additionally, we utilized a mouse model of eCRS to assess the impact of Sirt5 gene deletion on the disease. To further understand the underlying mechanisms, we conducted experiments at the single‐cell level using bone marrow‐derived eosinophils. We validated our findings through in vitro culture of eosinophils and intervention experiments. Through these experiments, we aimed to elucidate how Sirt5 regulates target proteins and reshapes their related metabolic pathways. Results There is a positive correlation between the severity of eCRS and the expression level of Sirt5 in nasal mucosa. Inhibiting Sirt5 expression can effectively alleviate the abnormal activation of eosinophils and the resulting inflammatory response in eCRS‐affected nasal mucosa. Sirt5 exerts its influence on eosinophil metabolism by negatively regulating the succinylation level of pkm2, a critical gene in the amino acid biosynthesis pathway. Conclusions The severity of eCRS is closely associated with the expression level of Sirt5. Sirt5 plays a negative regulatory role in the succinylation level of Pkm2 in eosinophils, thereby influencing metabolic remodeling and functional activation in eCRS. Investigating Sirt5 and its downstream metabolic pathways could offer valuable insights into the disease's pathogenesis and facilitate the development of targeted therapeutic strategies. This research holds significant implications for clinical practitioners involved in the diagnosis and treatment of patients with eCRS.